National poetry of Khawaja Dil Muhammad - Tehseen, Teyyeba (Makhz (Research Journal), 2024)
Urdu poetry has almost a century long tradition of those poems that bear the themes of patriotism and nationalism. These poems are replete with the themes of one’s love for one’s land, the desire for freedom, the praise for the beauty of one’s land and one’s love and admiration for one’s compatriots. The beginning of the twentieth century brought forth this kind of poetry in its wake. Urdu poetry of the twentieth century has such great names at its credit; for example: Altaf Hussain Hali, Akbar Ilah Abadi, Dr. Sir Muhammad Iqbal, Hasrat Mohani, Chakbast, Akhtar Sherani, Asrarul-Haq Majaz, Faiz Ahmed Faiz and Hafeez Jallundhari are few such poets to mention. Another name from this vast panorama is that of Khawaja Dill Muhammad’s who penned down beautiful national and patriotic poems. There is no doubt about the fact that these poems also paved way for the independence of the Indo-Pak subcontinent from the British Colonialism. Even after the independence of Country (1947), Khawaja Dill Muhammad’s Poems kept emerging as the unabashed paean of praise for his motherland. This research paper aims at focusing highlighting the salient features of Khawaja Dill Muhammad’s national and Patriotic poetry.